Developing a job accessibility standard for resettlement sites a case study of Pandi, Bulacan, the Philippines - Tsutsumi, Yuko (School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
This research attempts to present a job-accessibility standard for off-site resettlement planning in the Philippines by using a generalized transport cost model. People who were relocated outside Metro Manila endure high transport fare and long travel time. Resettlement policies by the World Bank and the Asian Development Bank require restoration of assets of relocates throughout the resettlement implementation. However, loss of accessibility was not taken into consideration by the said agencies. The Generalized Transport Cost Model was adopted as the method for accessibility standard. Three components of commuting job experience as accessibility measure were integrated into the generalized transport cost by converting these into monetary value: direct travel fare, travel time, and human effort. Direct travel fare is the amount passengers pay for public transport. Travel time is converted into monetary value based on the National Capital Region's minimum wage. Human effort or physical and mental exhaustion, is included in the coefficient of travel time. Human effort is measured by two criteria: how stressed commuters feel and how they perspire while traveling. As a result, it shows that the average general transport cost prior to relocation is for a one-way commute and after relocation Php 85 for a one-way commute and Php 373 after relocation. Due to the increased transports burden, number of relocates stay within Metro manila during weekdays. Commuters who travel on a daily basis pay a general transport cost of Php 224 for a one-way commute (this excludes workers who stay within Metro Manila). Acceptable travel cost for all respondents is Php 147. Acceptable walking time is 11 minutes, waiting time is 10 minutes, and in-transit time is 37 minutes. In order to fulfill the job-accessibility standard, walking distance from house to vehicle bay should be within 540 meters with a walking speed of 3km/h; headway of public transportation is 10 minutes and riding distance is 30 km with a driving speed of 50km/h; direct travel fare for public transport is Php 40; total cost for commuting one way must be set within a general transport cost of Php 147. Two policies are recommended to fulfill the presented job-accessibility standard: improvement of transport condition to make NCR accessible within the general transport cost of Php 147; and provision of income opportunities within a general transport cost of Php 147 provided that there is no change in the current transport condition. Alleviation of traffic congestion is an urgent need. Cash to compensate the general transport cost gap before and after relocation is also recommended, if the said policies are not feasible. Limitations include low response rate from men who work and travel characteristics should be the same even if the commute is not or work (i.e. travel to work and school).